FEATURES OF THE APPLICATION OF INNOVATIVE TOOLS IN THE MANAGEMENT OF ENTERPRISES IN THE AGRICULTURAL SECTOR OF THE ECONOMY - Oleksandr Kondrat (Соціально-економічні відносини в цифровому суспільстві)
The agricultural sector requires innovative management approaches to ensure competitiveness and sustainable development amid rising global food demand, resource constraints, and climate change. This paper analyzes the specific features of agricultural innovation management tools, focusing on three categories: digital technologies (such as precision farming systems and other AgriTech applications), financial instruments (including index-based crop insurance and fintech solutions), and organizational innovations (like clustering and modern cooperatives). The overarching goal is to evaluate how these innovations are being applied and their effects on the efficiency and resilience of agricultural production. The study adopts a mixed-method approach, combining a comprehensive literature review with an analysis of secondary statistical data. Data from international organizations (e.g., FAO, World Bank, USDA) were examined to assess current innovation adoption trends. The results indicate that innovations significantly improve agricultural productivity and resource efficiency. For example, precision farming tools can boost crop yields by around 4–6% and reduce input use (water, fuel, agrochemicals), lowering costs and environmental impacts while enabling producers to "do more with less." Likewise, modern financial instruments and organizational strategies (e.g., index insurance and farmer cooperatives) enhance producers' resilience to climate and market risks. However, the adoption of innovations is uneven: large high-tech enterprises embrace new tools much faster, whereas small farms often lag behind due to limited capital, skills gaps, and inadequate infrastructure—creating a growing innovation divide in the sector. This study provides a novel integrated perspective by systematically comparing technological, financial, and managerial innovations in agriculture, including global trends and specific cases from Ukraine. It synthesizes previously fragmented knowledge, reveals interactions between technological and organizational factors that were overlooked in earlier studies, and addresses how its findings differ from those of prior research. Finally, the paper proposes several recommendations to accelerate digital transformation and innovative development in the agricultural sector.